(untitled) (Itinera, 2017)
In this essay, I try a first attempt to match the reflection upon âdanceâ and âtasteâ. For this purpose, I take some examples from the repertory of the Tanztheater Wuppertal Pina Bausch. In my text, I consider the possibility to recognize an analogy between âdanceâ and âtasteâ from an epistemological perspective.